2017
DOI: 10.5430/ijhe.v6n6p170
|View full text |Cite
|
Sign up to set email alerts
|

Self-Construal and Demographic Variables as Predictors of Blind and Constructive Patriotism in University Students

Abstract: The aim of this study is to investigate the blind and constructive patriotism tendencies of university students in light of the demographic structure and variables. The investigation is performed by using the correlational descriptive model. The purposeful sampling technique has been used and data was collected from a total of 390 university students. 225 (57.7%) of the participants were female and 165 (42.3%) were male; the age group of participants ranged from 18 to 26 years with a mean age of 20.42 (SD = 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
1
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
2
1
1
1
Order By: Relevance
“…A public opinion survey of residents of Ukraine conducted by the Center for Insights in Survey Research (2022) showed that, amongst Russianspeaking Ukrainians, 51% were willing to fight against Russian invasion, compared to 61% among the Ukrainian-speaking population. In contrast to previous work which conducted among Turkish university students (Ercan, 2017), we failed to find sex differences in patriotism. This suggests that patriotic feelings may be held equally widely between the sexes during this time of intense conflict.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…A public opinion survey of residents of Ukraine conducted by the Center for Insights in Survey Research (2022) showed that, amongst Russianspeaking Ukrainians, 51% were willing to fight against Russian invasion, compared to 61% among the Ukrainian-speaking population. In contrast to previous work which conducted among Turkish university students (Ercan, 2017), we failed to find sex differences in patriotism. This suggests that patriotic feelings may be held equally widely between the sexes during this time of intense conflict.…”
Section: Discussioncontrasting
confidence: 99%
“…The present research focused on patriotic attitudes amongst the Ukrainian population during the Russian invasion of 2022. Patriotism has previously been positively associated with well-being, satisfying needs for security, being loved and respect (Ercan, 2017). In our study patriotism varied significantly across region, in line with previous work elsewhere identifying city-level variations in patriotism (Ercan, 2017), with patriotism in our data higher in non-Russophone areas (Kyiv, Central Regions, the West and North, compared to the East and South).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…If so, an emphasis on blind patriotism is to be expected. This assumption has some culturally appropriate and empirical support (Ercan 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Studi lain menghubungkan kiprah lembaga pendidikan dengan corak patriotisme, hasilnya mengungkapkan bahwa pendekatan yang terfokus pada prestasi negara, konformitas, dan tradisi semata pada konteks pendidikan di Turki dapat meningkatkan peluang terbentuknya pola patriotisme buta; berbeda dengan pendekatan yang terfokus pada universalisme dan stimulasi yang bisa meningkatkan peluang munculnya patriotisme konstruktif (Yazıcı, 2022). Hasil studi lain juga menyimpulkan bahwa faktor demografis dan aspek collective-self (bagaimana situasi ruang publik komunitas tempat asal mahasiswa) memengaruhi tendensi patriotisme (Ercan, 2017).…”
Section: Pendahuluanunclassified